Analysis Of Factors Affecting Earning Response Coefficient - Rakhmawati, Ita; Agustina, Laila Fajri (Jurnal Riset Akuntansi Terpadu, 2025)
This research tests the influence of five variables independent , namely risk systematic , capital structure, opportunity grow , size companies , and Islamic social reporting (ISR) regarding variable dependent , namely earning response coefficient (ERC). Earnings Response Coefficient (ERC) is coefficient that measures how much strong profit company influence price stocks . Research This use approach quantitative . Population from study This are 43 companies registered with JII during period 2020-2023. The sample was selected use method purposive sampling as much as 19 companies . Data analyzed use method panel data regression with Eviews 12 software assistance . Research results show that risk systematic influential significant in a way positive towards ERC, the opportunity grow influential significant in a way negative against ERC, size company influential significant in a way negative against ERC. While Capital structure and ISR are not influential against ERC